Reaching the hearts and minds of illiterate women in the Amhara highland of Ethiopia: Development and pre-testing of oral HIV/AIDS prevention messages - Gebeyehu W Bogale; Henk Boer; Erwin R Seydel (Taylor & Francis Group, 2010)
In the style of radio programmes, we developed three episodes of audio HIV prevention education for illiterate women in Ethiopia. We used social-oriented presentation formats, such as discussion between women on HIV prevention, and expert-oriented presentation formats, such as an interview with a male doctor. The aim of this study was to assess the relation between evaluation of presentation formats and overall liking of episodes, which is important for persuasive effects. Thirty women from rural Amhara listened to the episodes and, after listening, female data collectors interviewed the women on evaluation of presentation formats, overall liking of episodes, identification with the characters and convincingness. Evaluation of social-oriented presentation formats was strongly related to overall liking of episodes, but evaluation of expert-oriented presentation formats was not. This relation was mediated through convincingness and not through identification. We conclude that social-oriented presentation formats make messages more convincing and, consequently, improve overall liking and persuasive impact.